DAMPAK DIMENSI EKUITAS MEREK TERHADAP KEPUTUSAN PEMBELIAN ; STUDI EMPIRIS KONSUMEN MEREK ULTRA MILK DI WILAYAH DKI JAKARTA (The Impact of Brand Equity Dimensions on Purchase Decision: Empirical Study of Milk Consumers in DKI Jakarta) - DWIWIDYAWAN, JOHANNES ANDREW; ROSIANA, NIA (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2025)
The low level of milk consumption in Indonesia presents both a challenge and an opportunity for milk producers. Packaged milk has become a preferred choice among consumers due to its convenience. Although Ultra Milk is one of the pioneers of packaged milk in Indonesia, its ranking in the 2024 Top Brand Award declined. This study aims to examine the effect of brand equity on consumers' purchasing decisions for Ultra Milk in DKI Jakarta Province. The research uses descriptive, Likert-scale, and SEM-PLS methods. The result showed that brand awareness got the highest score, while brand loyalty received the lowest score. Furthermore, the SEM-PLS method analysis showed that brand equity has a positive and significant influence on purchasing decisions. The IPMA results show that brand loyalty demonstrates the weakest performance among the four brand equity dimensions.